ε-Polylysine inhibits Alternaria alternata through membrane-targeted antifungal activity and N-glycosylation modification - Wenhui Xu; Min Wang; Hao Jiang; Yangyang Sun; Yamin Du; Maorun Fu (Postharvest Biology and Technology, 2026)

Exciton regulation and directional electron transfer in artemisia-derived carbon dots/g-C3N4 heterojunction for enhanced visible-light photocatalytic antibacterial activity - Mingzhu Yuan; Weile Xie; Ran Qiu; Mingxin Zhou; Yangyang Li; Yuanxu Liu; Zibing Liu; Yupeng Yuan; Da Fu; Xiangang Lin (Chemical Engineering Journal, 2026)

Mechanism of Kushen Tongguan Pill on benign prostatic hyperplasia: roles of TLR4/NF-κB pathway and macrophage M1 polarization - Shaofeng Chen; Jie Wang; Yuhong Feng; Chunxu Li; Fu Wang; Lin Miao; Yaojun Li; Yangyang Lei; Qiang Geng; Zhong Li; Feng Zhao; Yuan Sun; et al. (Journal of Molecular Histology, 2026)

Quantifying responses of concurrent PM2.5-O3 pollution to their precursors in the Yangtze River Delta megacity Cluster of China - Mingliang Ma; Mengjiao Liu; Mengnan Liu; Yihong Jiao; Fei Meng; Pingjie Fu; Jingxue Bi; Tongshuai Rong; Yangyang Liu; Yuqiang Wang; Huaqiao Xing (Environment, Development and Sustainability, 2026)

Elevated CO₂ promotes the translocation and degradation of strobilurin fungicides in cucumber via coupled physiological and metabolic pathways - Xuan Wu; Yangyang Fu; Xinyue Wang; Shuaipeng Lu; Shihua Zhang; Yingchao Liu; Xiaoxiao Feng (Pesticide Biochemistry and Physiology, 2026)

Regulation of PINK1/Parkin signaling pathway by berberine mediates mitochondrial autophagy to intervene in the proliferation and metastasis of thyroid cancer - Xiang Geng; YangYang Sun; JinJin Fu; Liang Cao; Yuan Li (Molecular & Cellular Toxicology, 2026)

Activating valence oscillations in reconstructed high-entropy selenide for self-stabilized seawater oxidation through localized lattice oxygen redox - Hai Li; Xiaoliang Zhang; Yangyang Liu; Taiping Fang; Xue Zou; Gui Wang; Shun Wan; Hongliang Dong; Zihao Lu; Yufan Wu; Jinhui Fu; Luobin Cao; et al. (Science Bulletin, 2026)

Failure behavior and associated thermal and gas hazards of lithium-ion batteries under typical cargo-fire scenarios in air transport - Fei Li; Zengjiang Zou; Xu Huang; Xudong Cheng; Rong Qiu; Yangyang Fu (Process Safety and Environmental Protection, 2026)

The application of cold-adapted microorganisms in biphenyl biodegradation: Responses and mechanisms to environmental temperature fluctuations - Zefan Liu; Jinou Huang; Wei Li; Yangyang Jia; Yulong Fu; Chaofeng Shen (Journal of Environmental Sciences, 2026)

Performance assessment and recommendations for motor vehicle emission remote sensing equipment in megacity conditions: Insights from Beijing - Yangyang Cui; Dongdong Guo; Huawei Yi; Lijun Zhu; Jianglong Yang; Lijun Hao; Mingliang Fu; Aijun Shi; Lei Nie; Honglin Cao; Yuanrong Yu; Gen Zhang; et al. (Journal of Environmental Sciences, 2026)

The genesis and source of tight sandstone gas in the third member of Xujiahe Formation in Zitong Sag, NW Sichuan Basin: Constraints from geochemical evidence - Yong Li; Yangyang Zhang; Chao Zheng; Xiaojuan Wang; Aobo Zhang; Xiaoyan Fu; Wei Yang; Shijia Chen; Ruijie Chen; Guidong Yi (Journal of Asian Earth Sciences, 2026)

Patterns and drivers of critical soil moisture threshold across global tree species - Chaoqing Song; Yangyang Fu; Jingyu Yao; Shengnan Chen; Zheng Fu; Shangrong Lin; Jingping Wang; Wenfang Xu; Wenping Yuan (Agricultural and Forest Meteorology, 2026)

Impact of organic carbon composition on bacterial community assembly in organic and mineral soil layers under phosphorus addition in a Robinia pseudoacacia plantation - Ahejiang SAILIKE; Yujie LIANG; Rong FU; Hongjian HAO; Rong WANG; Ning PENG; Shicai LI; Zhouchang YU; Fangxin ZHENG; Wei ZHANG; Yangyang LIU; Peizhi YANG; et al. (Pedosphere, 2026)

Corrigendum to “Bacillus coagulans controls grass carp overwintering syndrome through the intestinal microbiota-metabolite-immunity network” [Fish Shellfish Immunol. 169 (2026) 111084] - Yangyang Zhang; Zehui Su; Hucheng Jiang; Yanhua Zhao; Fu Gao; Kai Cai; Shuguang Fang; Kun Hu (Fish & Shellfish Immunology, 2026)

Three cytochrome P450 genes contribute to chlorantraniliprole resistance in Phthorimaea absoluta with fitness costs - Lun Li; Zunzun Jia; Kaiyun Fu; Xinhua Ding; Jiahe Wu; Xiaowu Wang; Tursun. Ahmat; Weihua Jiang; Yangyang Yan; Xinyue Dong; Xiaoqin Ye; Yawen Li; et al. (Pesticide Biochemistry and Physiology, 2026)

A study on the hydraulic and pollutant removal performance of bioretention systems using plants and oyster shells - Yue Luo; Tengfei Fu; Yange Dong; Xiaoxiao Sun; Yangyang Han; Chunjing Liu; Wenxia Xie (Journal of Environmental Management, 2026)

Is expectation disconfirmation related to stakeholder satisfaction and willingness to engage in national parks? A case study of Shennongjia National Park in China - Yangyang Zhang; Zhen Fu; Yang Xiang; Chucai Peng; Mingjun Teng; Lixiong Zeng; Wanji Yang; Lei Pan; Pengcheng Wang (Forest Policy and Economics, 2026)

Analysis of the effects of different water based extinguishing agents on the electro-thermal performance of 26700 sodium-ion and lithium-ion batteries - Xu Huang; Fei Li; Limei Yan; Feng Xue; Xudong Cheng; Heping Zhang; Yangyang Fu (Process Safety and Environmental Protection, 2026)

Simulation on charging and dynamics of a flowing bacterial aerosol in parallel-rod dielectric barrier discharge - Liyang Zhang; Jiacun Wu; Zihao Feng; Kaiyue Wu; Yutai Li; Haiyun Luo; Xiaole Zhang; Yangyang Fu (Journal of Aerosol Science, 2026)

Bacillus coagulans controls grass carp overwintering syndrome through the intestinal microbiota-metabolite-immunity network - Yangyang Zhang; Zehui Su; Hucheng Jiang; Yanhua Zhao; Fu Gao; Kai Cai; Shuguang Fang; Kun Hu (Fish & Shellfish Immunology, 2026)

Progress of germanium recovery from lignite and its by-products - Yukun Huang; Haotian Xie; Qianyu Chen; Yijun Cao; Yangyang Fan; Weijun Peng; Wei Wang; Biao Fu (Chemical Engineering Journal, 2025)

RNA methylation and breast cancer: insights into m6A, m7G and m5C - Yuhan Dai; Shuhan Zhao; Huilin Chen; Wenxin Yu; Ziyi Fu; Yangyang Cui; Hui Xie (Molecular Biology Reports, 2025)

A Brief Outlook on the Preparation and Magnetic Properties of Iron Oxide Nanoparticles for Water Remediation - Younas Iqbal; Wencong Ma; Xuhui Li; Shenglei Fu; Asim Shahzad; Imtiaz Ahmad; Yangyang Wang; Muhammad Adil; Mohammad Abohashrh (Water, Air, & Soil Pollution, 2025)

The expanding horizons of antifreeze proteins from food science to multidisciplinary technological innovations - Yishan Fu; Yangyang Li; Song Liu; Jian Chen (Trends in Food Science & Technology, 2025)

Antibiotic resistance genes in multi-matrices of Chaohu Lake: Spatiotemporal variation and correlation with pesticides and PPCPs - Hao Yang; Hongwei Fu; Yutong Zhao; Run Li; Man Cao; Yi Liu; Yachao Ni; Wei Song; Yangyang Liang; Panyuan Cai; Wei Chang; Fangbiao Tao; et al. (Journal of Hazardous Materials, 2025)

A novel approach for using cobalt and manganese components in high-cobalt slag to develop MnCo2O4 electrodes for asymmetric supercapacitors - Yukun Huang; Zeying Wang; Rifan Chen; Chenyi Cao; Yangyang Fan; Biao Fu; Weijun Peng; Yijun Cao; Yong-Zheng Fang (Journal of Environmental Chemical Engineering, 2025)

Supplementation of exogenous RpfE facilitates polychlorinated biphenyl degradation in soil by stimulating endogenous rpfE expression and promoting cell growth - Hong Zou; Fengjun Xu; Xinyi Li; Yangyang Jia; Yulong Fu; Chaofeng Shen (Journal of Hazardous Materials, 2025)

White matter microstructural alterations and brain metabolism distributions in Parkinson’s disease - Mengjiao Wang; Yansong Liu; Wei Han; Yifeng Yang; Yuying Jiao; Yujie Hu; Yang Yang; Linhan Zhang; Yangyang Wang; Peng Fu; Changjiu Zhao (Brain Imaging and Behavior, 2025)

Novel amphiphilic magnetic nanocellulose-based phosphotungstic acid type ionic liquid catalysts for biodiesel production - Tao Wang; Yangyang Jiang; Xiqing Wang; Linan Sun; Jingru Zhao; Yujie Fu (Journal of Environmental Chemical Engineering, 2025)

Selective conversion of guaiacol to alkylphenols in supercritical ethanol over acid-modified and re-doped Mo/HBEA - Rundong Liu; Jinliang Yan; Wenwen Wang; Yangyang Lu; Zhiyu Li; Peng Fu (Fuel, 2025)

Unveiling environmental adaptability of magnetite-mediated Feammox system: Multiple pathways identification, metabolic responses and engineering potential analysis - Xiangzhuang Fu; Yangyang Li; Weiwei Huang; Dexin Wang; Chunping Yang; Hongjun Han (Chemical Engineering Journal, 2025)

Mechanical modeling of biofilm morphology variation induced by changes in environments and internal stress - Jiankun Wang; Jin Li; Jin Wu; Yangyang Tang; Zheng Zhang; Yumeng Fu; Xiaoling Wang (International Biodeterioration & Biodegradation, 2025)

Soil labile organic carbon and nitrate nitrogen are the main factors driving carbon-fixing pathways during vegetation restoration in the Loess Plateau, China - Yujie Liang; Rong Fu; Ahejiang Sailike; Hongjian Hao; Zhouchang Yu; Rong Wang; Ning Peng; Shicai Li; Wei Zhang; Yangyang Liu (Agriculture, Ecosystems & Environment, 2025)

Environmentally friendly non-saponification solvent extraction and separation process for RE(III) (RE = Eu, Gd and Tb) in acetic acid solution using HEHEHP/n-heptane - Xiaoyang Qu; Xuxia Zhang; Jian Li; Shangwan Fu; Kejia Liu; Yangyang Xie; Liuyimei Yang; Hui Zhang; Tao Qi (Hydrometallurgy, 2024)

A green europium-cerium redox flow battery with ultrahigh voltage and high performance - Yating Wu; Lei Zhou; Yangyang Xie; Yaobin Lai; Shangwan Fu; Xingchen Kang; Wenhui Shi; Jian Li; Xuxia Zhang; Kang Hu; Hui Zhang; Tao Qi (Chemical Engineering Journal, 2024)

Emulation and detection of physical faults and cyber-attacks on building energy systems through real-time hardware-in-the-loop experiments - Guowen Li; Lingyu Ren; Ojas Pradhan; Zheng O’Neill; Jin Wen; Zhiyao Yang; Yangyang Fu; Mengyuan Chu; Jiajing Huang; Teresa Wu; K. Selcuk Candan; Veronica Adetola; et al. (Energy and Buildings, 2024)

Mechanically strong SiC aerogels with broadband electromagnetic wave absorption enabled by hollow skeleton and interface engineering - Mingyuan Yan; Yuelei Pan; Pan He; Lunlun Gong; Yangyang Fu; Heping Zhang; Xudong Cheng (Chemical Engineering Journal, 2024)

Fluorinated plant activators induced dual-pathway signal transduction and long-lasting ROS burst in chloroplast - Qinjie Shi; Jianmian Fu; Yiqing Zhou; Yuanyuan Ji; Zhenjiang Zhao; Yangyang Yang; Youli Xiao; Xuhong Qian; Yufang Xu (Pesticide Biochemistry and Physiology, 2024)

Ancestral sequence reconstruction of the prokaryotic three-domain laccases for efficiently degrading polyethylene - Bo Zeng; Yishan Fu; Jiacai Ye; Penghui Yang; Shixiu Cui; Wenxuan Qiu; Yangyang Li; Taoxu Wu; Haiyun Zhang; Yachan Wang; Guocheng Du; Song Liu (Journal of Hazardous Materials, 2024)

A new strategy for clean utilization of zinc oxide dust: Preparation of spinel zinc ferrite by solid phase reaction and its catalytic degradation of organic wastewater - Yukun Huang; Xiaolei Chen; Yangyang Fan; Chongqing Wang; Yijun Cao; Weijun Peng; Biao Fu; Jiang Liu; Mingzhen Hu (Minerals Engineering, 2024)

Air disinfection by nanosecond pulsed DBD plasma - Liyang Zhang; Kai Wang; Kaiyue Wu; Yuntao Guo; Zhigang Liu; Dong Yang; Wenjin Zhang; Haiyun Luo; Yangyang Fu (Journal of Hazardous Materials, 2024)

Water use and mortality risk of four tropical canopy trees with different leaf phenology during the 2016 El Niño drought - Chaoqing Song; Wenfang Xu; Shengnan Chen; Yangyang Fu; Wenping Yuan (Agricultural and Forest Meteorology, 2024)

A dynamic von Mises-based model to evaluate the impact of urbanization and climate change on flood timing in Yangtze and Huaihe River Basins, China - Pengcheng Xu; Dong Wang; Yuankun Wang; Vijay P. Singh; Zhilang Zhang; Xiaosan Shang; Hongyuan Fang; Yangyang Xie; Gengxi Zhang; Saiyan Liu; Xiaolei Fu (Journal of Hydrology, 2024)

The hepatoprotective effects of plant-based foods based on the “gut–liver axis”: a prospective review - Qiongdan Hu; Wan Liao; Zhen Zhang; Sanjun Shi; Shuguang Hou; Ningping Ji; Xinjie Zhang; Qian Zhang; Yangyang Liao; Linghui Li; Zongping Zhu; Yi Chen; et al. (Critical Reviews in Food Science and Nutrition, 2023)

Maximum helical dichroism enabled by an exceptional point in non-Hermitian gradient metasurfaces - Xiao Li; Chuanjie Hu; Yuan Tian; Youwen Liu; Huanyang Chen; Yadong Xu; Ming-Hui Lu; Yangyang Fu (Science Bulletin, 2023)

Advances in nanocomposite organic coatings for hydraulic fracturing proppants - Juan Du; Qisheng Huang; Pingli Liu; Yangyang Fu; Xitang Lan; Xiang Chen; Jinming Liu; Xiao Lu (Gas Science and Engineering, 2023)

Multipath error mitigation method considering NLOS signal for high-precision GNSS data processing - Xuan Zou; Ruinan Fu; Jian Tang; Yawei Wang; Xiaoyun Fan; Zhiyuan Li; Chenlong Deng; Yangyang Li; Weiming Tang (GPS Solutions, 2023)

Adsorption mechanism of phosphorus on biomass ash modified with lanthanum immobilized by chitosan - Yangyang Jiang; Junzhen Di; Yiming Ma; Saiou Fu; Yanrong Dong; Bofu Yuan (Environmental Science and Pollution Research, 2023)

An improved method to determine the minimum extinguishing concentrations of ultrafine dry powder agents: Taking NaHCO3 and KHCO3 as examples - Junchao Zhao; Yangyang Fu; Song Lu; Guangbin Lu; Feng Xue; Heping Zhang (Process Safety and Environmental Protection, 2023)

Benchmarking high performance HVAC Rule-Based controls with advanced intelligent Controllers: A case study in a Multi-Zone system in Modelica - Xing Lu; Yangyang Fu; Zheng O'Neill (Energy and Buildings, 2023)

Impact of flow velocity on the heterogeneous reaction of SO2 over Fe2O3 - Yangyang Liu; Tao Wang; Qiuyue Ge; Zhuocheng Shi; Kejian Li; Kedong Gong; Lifang Xie; Wei Wang; Qianlong Wang; Jin Han; Hongbo Fu; Jianmin Chen; et al. (Atmospheric Environment, 2023)

Bioinspired SiC aerogels for super thermal insulation and adsorption with super-elasticity over 100,000 times compressions - Mingyuan Yan; Xudong Cheng; Long Shi; Yuelei Pan; Pan He; Zhongxin Zhang; Zhiyi Lun; Yangyang Fu; Heping Zhang (Chemical Engineering Journal, 2023)

Spatial transcriptome analysis of long non-coding RNAs reveals tissue specificity and functional roles in cancer - Kang Xu; Xiyun Jin; Ya Luo; Haozhe Zou; Dezhong Lv; Liping Wang; Limei Fu; Yangyang Cai; Tingting Shao; Yongsheng Li; Juan Xu (Journal of Zhejiang University-SCIENCE B, 2023)

The Role of PTEN/PI3K/AKT Signaling Pathway in Apoptosis of Liver Cells in Cocks with Manganese Toxicity - Liu Xiaofei; Hou Yan; Fu Yu; Fan Jing; Yangyang; Zhang Na (Biological Trace Element Research, 2022)

Identification and Characterization of Immunoglobulin T Heavy Chain in Large Yellow Croaker (Larimichthys crocea) - Yan Teng; Qiuling Fu; Yuanzhen Tan; Yangyang Ding; Yang Ding; Xinhua Chen (Fishes, 2022)
Three immunoglobulin (Ig) isotypes have been identified in teleosts, IgM, IgD, and IgT or IgZ. IgT, a new teleost Ig isotype, plays a vital role in mucosal immunity. However, information on molecular and functional characteristics of fish IgT is still limited. In this study, an IgT heavy chain (LcIgT) gene was cloned and characterized in large yellow croaker (Larimichthys crocea). Complete cDNA of LcIgT was 1930 bp in length, encoding a protein of 554 amino acids. The deduced LcIgT contains a VH region and only three CH regions (CH1, CH2, CH4), but no transmembrane region was predicted. Phylogenetic analysis showed that IgT heavy chain sequences from all fish species are grouped together. Homology comparison showed that LcIgT shares the highest amino acid identity of 58.73% with IgT heavy chain in Scophthalmus maximus. The VH domain of LcIgT has the highest identity of 72.50% with that of Scophthalmus maximus IgT. Relatively, each constant domain of LcIgT exhibits the highest amino acid identity with that of IgT in Oreochromis niloticus (67.61% identity for CH1, 61.11% identity for CH2, and 63.74% identity for CH4). LcIgT was constitutively expressed in various tissues tested, with the highest levels in mucosa-associated tissues such as gills and skin. After Cryptocaryon irritans infection, the mRNA levels of LcIgT were significantly up-regulated in the spleen (3.27-fold) at 4 d, in the head kidney (3.98-fold) and skin (2.11-fold) at 7 d, and in gills (4.45-fold) at 14 d. The protein levels in these detected tissues were all significantly up-regulated; the peak of its up-regulation was 6.33-fold at 28d in gills, 3.44-fold at 7d in skin, and 3.72-fold at 14d in spleen. These results showed that IgT response could be simultaneously induced in both systemic and mucosal tissues after parasitic infection and that IgT may be involved in systemic immunity and mucosal immunity against parasitic infection.

A review of microplastics in the aquatic environmental: distribution, transport, ecotoxicology, and toxicological mechanisms - Jia Du; Shaodan Xu; Qingwei Zhou; Huanxuan Li; Li Fu; Junhong Tang; Yangyang Wang; Xu Peng; Yuting Xu; Xinpeng Du (Environmental Science and Pollution Research, 2020)

A novel non-ATP competitive FGFR1 inhibitor with therapeutic potential on gastric cancer through inhibition of cell proliferation, survival and migration - Jianzhang Wu; Xiaojing Du; Wulan Li; Yangyang Zhou; Encheng Bai; Yanting Kang; Qiuxiang Chen; Weitao Fu; Di Yun; Qing Xu; Peihong Qiu; Rong Jin; et al. (Apoptosis, 2017)

Mining-induced ground movement in tectonic stress metal mines: a case study - Kaizong Xia; Congxin Chen; Xiumin Liu; Hua Fu; Yucong Pan; Yangyang Deng (Bulletin of Engineering Geology and the Environment, 2016)

CHD3 chromatin-remodeling factor PICKLE regulates floral transition partially via modulating LEAFY expression at the chromatin level in Arabidopsis - Xing Fu; Chaonan Li; Qing Liang; Yangyang Zhou; Hang He; Liu-Min Fan (Science China Life Sciences, 2016)

Do corticosteroids have a role in treating Ebola virus disease? - Jun Xu; DingYu Tan; YangYang Fu; Joseph Walline; XueZhong Yu (Science China Life Sciences, 2015)